Uro-Vaxom® : immunobiotherapy in urinary tract infections : basic information (Scientifíc Department OM Laboratories, 1989)
The booklet presents the results of toxicological, pharmacological, and clinical studies of URO-VAXOM, a new biological immunomodulator used in the treatment of urinary tract infections.
Keywords: biologická terapie; imunoterapie; biomedicínský výzkum; Immunotherapy; antibakteriální látky; farmacie a farmakologie; Biological Therapy; Biomedical Research; Anti-Bacterial Agents; urologie; Uro-Vaxom; infekce močového ústrojí; Urinary Tract Infections